Physicians' perspectives on medication adherence and health promotion among cancer survivors. Issue 23 (26th August 2019) - Stump, Tammy K.; Robinson, June K.; Yanez, Betina; Penedo, Frank; Ezeofor, Adaeze; Kircher, Sheetal; Spring, Bonnie
Abstract : Background: Cancer survivors face an increased risk of cardiovascular events compared with the general population. Adopting a healthy lifestyle may reduce these risks, and guidelines encourage health‐promotion counseling for cancer survivors, but the extent of physician adherence is unclear. Methods: This mixed‐method study surveyed 91 physicians, including 30 primary care physicians (PCPs), 30 oncologists, and 31 specialists (urologists, dermatologists, and gynecologists). Interviews also were conducted with 12 oncologists. Results: Most PCPs (90%) reported recommending health promotion (eg, weight loss, smoking cessation) to at least some cancer survivors, whereas few oncologists (26.7%) and specialists (9.7%) said they ever did so ( P < .001). Although most physicians believed that at least 50% of cancer survivors would be adherent to medication regimens to prevent cancer recurrence, they also believed that, if patients were trying to lose weight, they would not remain medication‐adherent. In interviews, oncologists expressed fear that providing health‐promotion advice would distress or overwhelm patients. Additional health‐promotion barriers identified by thematic analysis included: identifying cancer as oncologists' focal concern, time pressure, insufficient behavior change training, and care coordination challenges. Facilitators included perceiving a patient benefit and having health‐promotion resources integrated into the cancer care system. Conclusions: Physicians often do not have the time, expertise, or resources to address health promotion with cancer survivors. Research is needed to evaluate whether health‐promotion efforts compromise medical regimen adherence, as physicians' responses suggest. Abstract : Survey responses from primary care physicians (n = 30), oncologists (n = 30), and other specialists who treat patients with cancer (n = 31), along with interviews of 12 oncologists, indicate that physicians do not often engage in healthy lifestyle promotion with cancer survivors and fear that providing health‐promotion advice would distress or overwhelm patients, compromising their medical regimen adherence. Additional health‐promotion barriers include perceived patient disinterest, cancer as oncologists' focal concern, time pressure, insufficient behavior change training, and care coordination challenges.